Comparative study to analyse the correlation between dermatoglyphics and impacted teeth - D N S V Ramesh; R Thriveni; Bellam B Rachel; P Manshi; Amit Byatnal; Pragati Kempwade (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Dental impaction is a serious challenge to the dental practitioners. Treatment for impaction is a complex procedure. During embryogenesis, the ridged skin and teeth develop from the same layer,. hence, suggesting that the genetic information in the genome is dissipated during this period, and any disturbance affecting tooth development and structure will be simultaneously reflected through change in dermatoglyphic patterns. This study aims to analyse the correlation between dermatoglyphics pattern variations and impacted teeth. Settings and Design: 100 patients, 50 impacted and 50 healthy patients, were selected who are attending to the department of oral medicine and radiology between the age group of 18-40 years. Methods and Materials: The fingerprints of both the hands were obtained using the duplicating ink pad. The fingertip patterns were analysed according to the classical method, and configurational types were classified according to the topological method. Statistical Analysis: The data obtained were subjected to statistical analysis using SPSS version 20.0 and the test of proportion and Chi-square test was used for the analysis. Results: Whorl type of fingerprints were observed more in impacted teeth patients whereas loop type of fingerprints was observed more in healthy patients. Conclusions: There is a significant correlation between impacted teeth and Dermatoglyphics and it can be used as a predilection marker.